(3GdaJGhi GdeMehOjIs - (3eMehO MeRI, eMehO Hf eMeO Hf fSjH, J (B1305 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Pj GdEMSGf hGdfYe Ke GdUdGI Ydi GdeNJGQ ddCee (B- (3aGdfXe CbQH CNPG YfO WGdHg hCSCd Gddg JMSHfG deNJJe (B- (3dPGc fXeJ ef NjQ GdeSGFd eG jchf faY HgG ddMGPb Gdages
(3BNQgG (B:s
(3UM hEf aj jheg de jQLY jdReg GKfGf dNda CeI (B- (3eSfG LQOGQ HCda YGeG Ke GfbVi hdeDLQ CYWi eGFI (B- (3Yf SfI bGHdI EjLGQg efYbO HMSGHgG Jdc GdeGFIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 185s
(3eYLe GdeDdajf (B3 / 830s
(3gOjI GdYGQajf (B2 / 420s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdMfHdjs